Konvergensi di Ruang Redaksi pada Kelompok Media Tempo - Pratopo, Wahyudi Marhaen; Kusajibrata, Nasrullah (Jurnal Studi Komunikasi, 2018)
This study seeks to reveal the implementation of convergence in the newsroom with case study of Tempo Group. This research uses qualitative approach and case study method. This study reveals that Tempo began to implement newroom convergence after publishing Kora Tempo in 2001. The effort toward newsroom convergence was realized by forming Tempo Newsroom which is meant as a news control center. After passing a series of trials and policy changes, the Tempo Group finally adopted full editorial convergence since 2012. In the application of this editorial convergence, Tempo chose the Newsroom 3.0 model, a newsroom management system that brings together news gathering and news processing to provide news needs for some outlet: tempo.co, Koran Tempo, and Tempo Magazine.